Pengaruh Suhu dan Lama Penyimpanan terhadap Mutu Benih Jagung Manis (Zea Mays Saccharata Sturt): Penelitian - Rivaldi, Rizki; Wijayanto, Budi; Khoiriyah, Annisa (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The deterioration of seeds is accelerated by improper storage temperatures. This research has the objective of: 1) Determine the best storage temperature for the quality of sweet corn seeds of the Nusa 1 variety. 2) To know the best storage time for the quality of sweet corn seeds of the Nusa 1 variety. 3) To determine the temperature intraction and length of storage time for the quality of sweet corn seeds of the Nusa 1 variety. This study applies a Divided Plot Design with the main plot being the temperature of the storage room consisting of the temperature of the cold storage room (13-23°C), refrigerator (6-7°C), and ordinary warehouse (28-30°C). A subplot is a storage time length consisting of 60 days, 90 days, and 120 days. The results of the data analysis showed that: 1) The temperature of the ordinary warehouse storage room showed the best quality of sweet corn seeds during storage. 2) The length of storage time of 60 days shows the best quality of sweet corn seeds during storage. 3) There is an interaction between temperature and storage time on the quality of sweet corn seeds.